Designing of uwb pulse generation in fpga based on delay line method for human range through the wall detecting application - Tantiparimongkol, Lalida; Phasukkit, Pattarapong (My University, 2019)
This paper intends to present UWB generation by FPGA for further using in human detecting through the wall. In this experiment, we use method of digital circuit synthesize by Verilog coding into FPGA. Which coding method is the implementation of Delay line based theory. This experiment could produce pulse with pulse width 575ps and bandwidth of 3.83GHz. The purpose is applied for radar through the wall for human range detection application. There're experiment with human detection system which locate human movement from Doppler frequency and standard deviation. The experiment is shown at range of detection at 1m, 1.5m and 2m which the result shows output pulse from FPGA could detect human at these ranges.
Keywords: Doppler frequency; FPGA; Human detection; Through the wall; Transmitting system; UWB generation